Towards noise classification of road pavements - Freitas, Elisabete F. (2008)
Noise classification of road surfaces has been addressed in many European countries. This paper presents the first approach towards noise classification of Portuguese road pavements. In this early stage, it aims at establishing guidelines for decision makers to support their noise reduction policies and the development of a classification system adapted to the European recommendations. A ranking to provide guidance on tire-road noise emission levels for immediate use by decision makers, road authorities, contracting parties and environmental officers will be established. This research was based on the results provided by three early studies covering more than ten different surfaces, among which, rubberized asphalt and experimental non conventional surfaces with optimized grading. On each road trial, the tire-road noise generated by light vehicles and heavy trucks at three speed levels were measured by means of the Controlled Pass-By method (CPB). Three of these runs were also tested by the Close ProXimity method (CPX). Additionally, tests to characterize texture and skid resistance were performed. The early noise classification studies of road pavements focused only on the CPB tests. Three groups with similar acoustical performance were identified. Noise level abatements of about 10 dB were achieved for the gap graded mixtures with a maximum aggregate size inferior to 10 mm.